Making Sense of Muslim Fundamentalisms: The Clash Within Islam - Hurvitz, Nimrod (Taylor & Francis Group, 2020)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgements -- Introduction -- PART I: Histories -- 1. Moderate fundamentalists -- 2. Militant fundamentalists -- PART II: Mobilization -- 3. Authority and leadership -- 4. The art and means of persuasion -- PART III: Moral order -- 5. Images of the West -- 6. Culture wars -- 7. Women in the public sphere -- 8. Concluding observations -- Index.